Analysis of a personal series of 500 cholecystectomies with conventional technique - Czarnevicz, Daniel; Fernández, Ricardo; Rodríguez, Gustavo; Praderi, Raúl (Cirugía del Uruguay, 1992)
The author analyses a personal series of 500 cholecystectomies. pointing out the /ow proportion of residual lithiasis (0.4%). and absence of mortality. The importance of technical systematization and intraoperative cholangiography is a/so emphasized